EU researchers saw brexit coming. (Research'eu results magazine)
Following the United Kingdom's decision to leave the European Union on 23 June 2016, the EU-funded SENSEI project has revealed that it accurately predicted the result of the referendum by analysing 6 million social media conversations in the weeks preceding the vote.